Pengembangan Model Manajemen Kinerja Pemerintah Berbasis Balanced Scorecard (Study Kasus Pemerintah Desa Mendana Raya) - Muhammad Rijalul Hadi; Saipul Arni Muhsyaf; Baiq. Rosiyda Dwi Astuti (Universitas Medan Area, 2022)
This article aims to build a government performance management model in Mendana Raya Village. In this study, the researcher used agency theory, which in general this theory provides a disclosure. This research uses Mixed Method Research with data collection techniques in the form of interviews and questionnaires, all of which are processed using Analytical Network Process techniques with the help of Super Decicion software. The results showed that the internal business perspective became the first priority followed by the customer perspective which became the second priority, then growth and learning became the third priority and finally the financial perspective became the fourth priority. Each strategy contained in the four perspectives is interrelated and contributes to each other. The results of this strategic priority measurement are expected to be a reference for the Mendana Raya Village government in achieving its goals.